Water use and response of a dry-farmed olive orchard recently converted to irrigation - Santos, Francisco Lúcio (2007)
Experimental results obtained in Southern Portugal from a dry-farmed mature olive tree orchard recently converted to drip irrigation are described. Water use and response to two irrigation management practices by olive trees was monitored with sap flow compensation heat pulse sensors, ‘Watermark’ granular matrix block sensors and a capacitance probe. The 80-plus-year-old mature olive tree orchard planted on a 12 m by 12 m spacing layout was converted in 2005 from dry-farming to drip irrigation and subjected to two water treatments: trees irrigated daily to supply for crop water demand and trees irrigated before-flowering, during pit-hardening and before crop-harvesting. Sap flow sensors were implanted in sample trees at three different positions around the trunk and measurements were taken at 30 min intervals during 4 months, from April to mid-August of 2005. Tree transpiration rates were estimated as average of sap flow rates. When trees were fully irrigated, the observed differences in daily sap flow rate amplitude were explained by the natural trees difference in canopy cover, plant height and conductance of water vapour sites. However, when deficit irrigation was prescribed and, when the trees stopped being irrigated, they gradually lost their ability to adequately respond to the evaporative demands of the day, showing smaller variations in amplitudes sap flow. After irrigation ceased in May 15, transpiration rate gradually decreased from its maximum of 7 l h−1, when trees were fully irrigated and soil water content was near to field capacity, to values of less than 3 l h−1 by July 3 as the soil water content gradually acted as the transpiration limiting factor. Transpiration rates recovered after irrigation was re-introduced on July 4. Although low in the non-irrigation period, transpiration rates never dropped to zero and stayed between 37 and 50 l d−1 from May 27 to June 9, as trees were able to extract soil water in the absence of irrigation. Olive trees maintained transpiration to levels as high as 50 l d−1 suggesting that long after irrigation is suppressed, a considerable amount of water held in the soil is made available to the trees. Differences in evapotranspiration and transpiration rates during the same period also indicated that olive trees, making use of the extensive root system developed in the 12 m by 12 m tree spacing, were able to extract soil water and maintain transpiration levels as high as 50 l d−1, while soil water balance indicated tree evapotranspiration rates close to zero. This particular ability of dry-farmed olive trees to remove water held in the soil under adverse conditions of very low soil moisture and uncertainties associated with the real volume of soil effectively explored by the root system, make profile probe sensors, regardless of their accuracy, unsuitable for control of water uptake and management of dry-farmed olive orchards recently converted to irrigation. Likewise, watermark sensors, able to capture the variations of high soil water, failed to provide meaningfully values below 0.28 cm3 cm−1. Both sensors should be used with care in managing irrigation of olive tree orchards and, rather than relying on soil moisture status, monitoring tree water-use and response with the compensation heat-pulse method seems a more appropriate approach